Properties of \Phi \left ( t,\tau \right ).
We developed Picard for solution of linear time varying x^{\prime }=A\left ( t\right ) x in the last two lectures. Established: That solution exist and the solution is unique. Some disadvantages of Picard method are
To find closed form solution, we need to obtain what is called the fundamental matrix. Let X^{01},X^{02},\cdots ,X^{0n} be n linearly independent initial conditions for a system with n states. For example, for n=3, always take these as X^{01}=\begin{pmatrix} 1\\ 0\\ 0 \end{pmatrix} ,X^{02}=\begin{pmatrix} 0\\ 1\\ 0 \end{pmatrix} ,X^{03}=\begin{pmatrix} 0\\ 0\\ 1 \end{pmatrix} and so on for more states. For each one of these X^{0i}, let \Psi ^{i} be the corresponding solution of x^{\prime }=A\left ( t\right ) x. i.e. \Psi ^{1}\left ( 0\right ) =X^{01},\Psi ^{2}\left ( 0\right ) =X^{02},\Psi ^{3}\left ( 0\right ) =X^{03}. i.e. \dot{\Psi }^{i}\left ( t\right ) =A\left ( t\right ) \Psi ^{i}\left ( t\right ) Now form the fundamental matrix solution \Psi \left ( t\right ) =\begin{pmatrix} \Psi ^{1}\left ( t\right ) & \Psi ^{2}\left ( t\right ) & \cdots & \Psi ^{n}\left ( t\right ) \end{pmatrix} Each \Psi ^{i} is n\times 1, and there are n such columns, hence \Psi \left ( t\right ) is n\times n matrix. Any solution can now be found with the help of this \Psi \left ( t\right ) , for any initial conditions. Remark: Matrix \Psi \left ( t\right ) satisfies the state equation. \Psi ^{\prime }\left ( t\right ) =A\left ( t\right ) \Psi \left ( t\right ) At t=0,\Psi \left ( 0\right ) has n linearly independent columns by construction. What about for t>0?
Reader: Show that \Psi \left ( t\right ) has n linearly independent columns for t>0. Proof: By contradiction. Assume at t^{\ast } , \Psi \left ( t^{\ast }\right ) no longer has linearly independent columns. Then there exist vector \vec{x}\left ( t^{\ast }\right ) not zero s.t. \Psi \left ( t^{\ast }\right ) \vec{x}\left ( t^{\ast }\right ) =\vec{0}. This implies that x^{\prime }\left ( t^{\ast }\right ) =0, which means that x\left ( t\right ) =0, hence contradiction.
Example: Let x_{1}^{\prime }=x_{1}+tx_{2},x_{2}^{\prime }=x_{2}. Hence x^{\prime }=\begin{pmatrix} 1 & t\\ 0 & 1 \end{pmatrix}\begin{pmatrix} x_{1}\\ x_{2}\end{pmatrix} . Now let X^{01}=\begin{pmatrix} 1\\ 0 \end{pmatrix} to be one linearly independent initial conditions. We use this to solve the state equation. Next to use the second X^{02}=\begin{pmatrix} 0\\ 1 \end{pmatrix} and repeat the process. So we end up with two solutions. These make up \Psi matrix. Using X^{01}, we see that x_{1}\left ( 0\right ) =1,x_{2}\left ( 0\right ) =0. Now we solve the state equation. x_{1}^{\prime }=x_{1}+tx_{2},x_{2}^{\prime }=x_{2}\left ( t\right ) . This results in \Psi ^{1}\left ( t\right ) =\begin{pmatrix} e^{t}\\ 0 \end{pmatrix} . Now using initial conditions x_{1}\left ( 0\right ) =0,x_{2}\left ( 0\right ) =1 we solve the same state equation again, this results in \Psi ^{2}\left ( t\right ) =\begin{pmatrix} \frac{1}{2}t^{2}e^{t}\\ e^{t}\end{pmatrix} , hence \Psi \left ( t\right ) =\begin{pmatrix} e^{t} & \frac{1}{2}t^{2}e^{t}\\ 0 & e^{t}\end{pmatrix}
Now that we have found \Psi \left ( t\right ) we need to find the general solution to x^{\prime }=A\left ( t\right ) x\left ( t\right ) +B\left ( t\right ) u with given any x\left ( 0\right ) (this initial condition has nothing to do with X^{0i} used to find \Psi \left ( t\right ) , this is the actual initial condition for the problem itself.
Assume the general solution is x\left ( t\right ) =\Psi \left ( t\right ) \theta \left ( t\right ) where \theta \left ( t\right ) is some function to be found. Plugging this solution into the state space equation, we obtain \Psi ^{\prime }\left ( t\right ) \theta \left ( t\right ) +\Psi \left ( t\right ) \theta ^{\prime }\left ( t\right ) =A\left ( t\right ) \Psi \left ( t\right ) \theta \left ( t\right ) +B\left ( t\right ) u But \Psi ^{\prime }\left ( t\right ) =A\left ( t\right ) \Psi \left ( t\right ) , so the above simplifies to\begin{align*} \Psi \left ( t\right ) \theta ^{\prime }\left ( t\right ) & =B\left ( t\right ) u\\ \theta ^{\prime }\left ( t\right ) & =\Psi ^{-1}\left ( t\right ) B\left ( t\right ) u \end{align*}
Integrating \theta \left ( t\right ) -\theta \left ( 0\right ) ={\displaystyle \int \limits _{0}^{t}} \Psi ^{-1}\left ( \tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau But \theta \left ( 0\right ) =\Psi ^{-1}\left ( 0\right ) X\left ( 0\right ) where X\left ( 0\right ) is the initial conditions. (why??). Hence the above becomes \theta \left ( t\right ) =\Psi ^{-1}\left ( 0\right ) X\left ( 0\right ) +{\displaystyle \int \limits _{0}^{t}} \Psi ^{-1}\left ( \tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau Therefore, since x\left ( t\right ) =\Psi \left ( t\right ) \theta \left ( t\right ) \,. Then\begin{align*} x\left ( t\right ) & =\Psi \left ( t\right ) \left ( \Psi ^{-1}\left ( 0\right ) X\left ( 0\right ) +{\displaystyle \int \limits _{0}^{t}} \Psi ^{-1}\left ( \tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau \right ) \\ & =\Psi \left ( t\right ) \Psi ^{-1}\left ( 0\right ) X\left ( 0\right ) +\Psi \left ( t\right ){\displaystyle \int \limits _{0}^{t}} \Psi ^{-1}\left ( \tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau \\ & =\Psi \left ( t\right ) \Psi ^{-1}\left ( 0\right ) X\left ( 0\right ) +{\displaystyle \int \limits _{0}^{t}} \Psi \left ( t\right ) \Psi ^{-1}\left ( \tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau \end{align*}
Let \Psi \left ( t\right ) \Psi ^{-1}\left ( \tau \right ) =\Phi \left ( t,\tau \right ) called the transition matrix, then the above becomes \fbox{$x\left ( t\right ) =\Phi \left ( t,0\right ) X\left ( 0\right ) +{\displaystyle \int \limits _0^t} \Phi \left ( t,\tau \right ) B\left ( \tau \right ) u\left ( \tau \right ) d\tau $} Reader: Find \Phi \left ( t,\tau \right ) for the last example, and then find x\left ( t\right ) for unit step u\left ( t\right ) .
Properties of \Phi (t,\tau ):
side note: Remember this \frac{\partial }{\partial t}{\displaystyle \int \limits _{t_{0}}^{t}} f\left ( t,\tau \right ) d\tau ={\displaystyle \int \limits _{t_{0}}^{t}} \frac{\partial }{\partial t}f\left ( t,\tau \right ) d\tau +\left . f\left ( t,\tau \right ) \right \vert _{\tau =t}